Yrityshistoria ja kasvuyrittäjyys - Jensen-Eriksen, Niklas (Annales Academiae Scientiarum Fennicae, 2023)
In recent years, there has been lively discussion in Finland on why the country does not have more young and fast-growing companies. These debates usually lack historical perspective. Entrepreneurship has always existed in Finland. Yet, the operational environment, values, gender roles and social structures have had an impact throughout history on who is willing and able to establish a company. These factors also influence the ability and willingness of new companies to grow. History can provide us with insights into why the Finnish economy has certain weaknesses, for example a lack of economic and social diversity and a shortage of old and successful middle-sized companies as well as younger high-growth companies. The most successful startup period in Finland was 1850–1914. Many of the companies founded during that time grew quite large. Since then, it has been more difficult for the country to replicate this early success.